(untitled) (Revista de História Regional, 2007)
From the thirties, the radio in São Paulo ask for establishing itself as an important point of reference in the cultural life of the city. Abandoned a kind of impersonal upper-class style, a characteristic of its first years, the broadcasting tried, little by little, to reach wider strata of the population, redefining its role. As the number of stations increased, subsequently reception enlarged, there was a meaningfully diversification in their programs. This study intends to consider the broadcasting enlargement as a way that shows the transformation of the city into a metropolis.